Industrial Clusters, Migrant Workers, and Labour Markets in India - Uchikawa, Shuji. (IDE-JETRO Series, 2014)
This book analyzes three points: employment conditions for migrant workers, the impact of industrialization as part of industrial clusters upon surrounding and outlying villages, and the labour market in industrial clusters. This book examines the cases of two newly developed industrial clusters: Ludhiana in Punjab and Tiruppur in Tamil Nadu.